2018
DOI: 10.15244/pjoes/81615
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Forest Road Construction on Topsoil Erosion and Hydro-Physical Soil Properties in a Semi-Arid Mountainous Ecosystem in Turkey

Abstract: This study aimed at pointing out the environmental importance of road construction in a semi-arid high mountainous area on soil erosion and some important soil properties throughout the forest road. In total 60 soil samples in both forest and open area were collected from topsoil (0-20 cm) of a cut slope, fill slope, and control points along with a forest road route. The soil properties were determined in the laboratory and the soil loss amounts were determined by way of an Allgemeine Boden Abtrags Gleichung (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The values obtained in the present study were lower than those in other studies. In some studies, when the amount of sediment loss in cutslopes and fillslopes was compared, more losses were found in the cutslopes [6,10,36]. However, one study reported that 60% of the sediments from roads are caused by fillslopes, 25% by the road surface and 15% by cutslopes [12].…”
Section: Amount Of Runoff and Suspended Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…The values obtained in the present study were lower than those in other studies. In some studies, when the amount of sediment loss in cutslopes and fillslopes was compared, more losses were found in the cutslopes [6,10,36]. However, one study reported that 60% of the sediments from roads are caused by fillslopes, 25% by the road surface and 15% by cutslopes [12].…”
Section: Amount Of Runoff and Suspended Sedimentmentioning
confidence: 99%
“…Usually, the main reason for increased erosion after the construction of forest roads can be listed as the elimination, in part or as a whole, of the protective flora along the way [5][6][7]. In addition, with increased cutslope length there is also an increasing rate of soil loss [8][9][10]. Moreover, possible causes of the accelerated erosion, which may take place following road construction on forested lands, include destruction or impairment of the natural soil structure and fertility, increased slope gradients created by the construction of cutslopes and fillslopes, decreased infiltration rates on parts of the road, interception of subsurface flow by the road cut gradient, decreased shear strength, increased shear stress, cutslopes and/or fillslopes, and concentration of generated and intercepted water [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The values obtained in the present study were lower than those in other studies. In some studies, when the amount of sediment loss in cutslopes and fillslopes was compared, more losses were found in the cut slopes [30][31][32]12]. However, it has been reported that 60% of the sediments from roads are caused by fillslopes, 25% by the road surface and 15% by cutslopes.…”
Section: Amount Of Runoff and Suspended Sedimentmentioning
confidence: 99%
“…Usually the main reason for increased erosion after the construction of forest roads can be listed as the elimination, in part or in whole, of the protective flora along the way [7][8][9]. In addition, with increased cutslope length there is also an increasing rate of soil loss [10][11][12]. Moreover, possible causes of the accelerated erosion which may take place following road construction on forested lands include destruction or impairment of the natural soil structure and fertility, increased slope gradients created by construction of cutslopes and fillslopes , decreased infiltration rates on parts of the road, interception of subsurface flow by the road cut slope, decreased shear strength, increased shear stress, cutslopes and/or fillslopes, and concentration of generated and intercepted water [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The different erosive processes, either natural or caused by human activity, cause different materials to be moved and deposited in other areas where they did not exist before [2]. Human activities accelerate the process of erosion [3] and export of sediments through which they convert the soil into a non-renewable resource.…”
mentioning
confidence: 99%